АКАДЕМИК ЛИЦЕЙЛАРДА МАТЕМАТИК АНАЛИЗ АСОСЛАРИНИ ЎҚИТИШДА УЗВИЙЛИКНИ ТАЪМИНЛОВЧИ ЎҚИТИШ МЕТОДИКАСИНИНГ САМАРАДОРЛИГИ ҲАҚИДА - Алламбергенов, И.Х. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of succession maintenance between grade levels in the Methods of teaching Mathematics, the tasks of providing the succession through formation of mathematical skills, definition of criterion of succession maintenance, and the basic components of methods of teaching.
Keywords: mathematical analysis; academic lyceum; continuity; criteria; component; skills; independent work; theoreme; conditions; non-standard ways